Investigating Financial Reporting Fraud Using Fraud Pentagon Theory to Strengthen Governance and Transparency - Shodiq, Muhammad Ja'far; Ermawati, Ermawati; Rosalina, Rita; Khatamy, Azizah Azmi (Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines fraudulent financial reporting in Indonesia using the Fraud Pentagon Theory, which incorporates financial targets, stability, external pressure, ineffective monitoring, changes in auditors and directors, and CEO photo frequency as determinants. It addresses gaps in prior research that predominantly relied on the Fraud Triangle and Fraud Diamond frameworks, emphasizing large corporations while neglecting small and medium-sized enterprises (SMEs). The study employs a purposive sampling method, selecting 190 State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Multiple linear regression analysis was used to assess the relationship between independent variables and fraudulent financial reporting. The findings confirm that Financial Target, Financial Stability, External Pressure, Ineffective Monitoring, Changes in Auditors, Changes in Directors, and CEO Photo Frequency significantly impact fraudulent financial reporting, whereas firm size does not. These results align with agency theory, highlighting the pressure on management to meet financial goals, leading to fraudulent activities. Thus, strengthening governance structures, enhancing auditor independence, and improving monitoring mechanisms are critical for mitigating fraudulent financial reporting. Future research should explore corporate culture, ethical leadership, and machine learning techniques to enhance fraud detection. Expanding studies across industries and regions can provide a broader understanding of financial fraud dynamics.